2021
DOI: 10.31219/osf.io/7s39r
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developmental Origins of Anti-Black Bias in White Children in the United States: Exposure to and Beliefs about Racial Inequality

Abstract: Anti-Black racism remains a pervasive crisis in the United States today. Racist social systems are rooted in prejudicial beliefs that reinforce and perpetuate racial inequalities. These beliefs have their developmental origins in early childhood and are difficult to change once entrenched in adolescence and adulthood. What causes children to form prejudicial beliefs and racial biases—and what steps can be taken to preempt them from forming—remain open questions. Here we show that children’s exposure to and bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The researchers found that 4-year olds’ beliefs that their parents and peers do not value interracial friendships predicted increased racial bias. This study reveals the importance not only of interracial friendships but the belief that parents and peers support these types of relationships, even as early as 4 years of age (Rizzo et al, 2021).…”
Section: Do Cross-race/ethnic Friendships Reduce Prejudice?mentioning
confidence: 84%
See 3 more Smart Citations
“…The researchers found that 4-year olds’ beliefs that their parents and peers do not value interracial friendships predicted increased racial bias. This study reveals the importance not only of interracial friendships but the belief that parents and peers support these types of relationships, even as early as 4 years of age (Rizzo et al, 2021).…”
Section: Do Cross-race/ethnic Friendships Reduce Prejudice?mentioning
confidence: 84%
“…In sum, even preschool-aged children are aware of racial categories (Rizzo et al, 2021; Shutts, 2015), can select friends based on race (Romero et al, 2009), and reliably report intergroup attitudes (Dunham et al, 2013). Moreover, age-appropriate novel measures have been created to examine these processes.…”
Section: Do Cross-race/ethnic Friendships Reduce Prejudice?mentioning
confidence: 99%
See 2 more Smart Citations
“…In childhood, target groups include gender, race, ethnicity, sexual identity, nationality, immigrant status, religion, and socioeconomic status (Levy, et al, 2016). Prejudicial attitudes toward these various target groups manifest when children are forming friendships and group identities (Elenbaas et al, 2016), revealing implicit and explicit bias (Rizzo et al, 2021; Rutland et al, 2005) as well as stereotypic expectations (Durante & Fiske, 2017; Mulvey & Killen, 2015). Prejudicial attitudes emerge during the preschool period, albeit inconsistently, change throughout childhood, vary by target groups, and are more malleable in childhood than in adulthood.…”
Section: Promoting Fair and Just School Environments: Developing In...mentioning
confidence: 99%